Promised [large type] - Garriott, Leah (Thorndike Press large print clean reads., 2020)
"Warwickshire, England, 1812. Fooled by love once before, Margaret vows never to be played the fool again. But then she finds that her father has promised her hand in marriage to Lord Williams, who is condescending and high-handed. Margaret will never consent to marrying such an odious man. Yet as Lord Williams inserts himself into her everyday life, proving himself intelligent and even kind, Margaret realizes that he is exactly the man she'd hoped to marry before she'd learned how much love hurt. Margaret is faced with her ultimate choice: keep the promises that protect her or break free of them for one more chance at love. Either way, she fears her heart will lose."--Back cover.